Standard Operating Procedures (SOPs) for Implementation of National Credit Framework (NCrF) in Higher Education - Dr. H. M. Naveen (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The Standard Operating Procedures (SOPs) notified by the UGC for operationalising the NCrF marks a significant step towards our shared vision of a lifelong education system that empowers learners with relevant skills and knowledge. The NCrF enables creditisation of all forms of learning from the school level onwards and ensures mobility between vocational education, training and skilling to general education and vice versa. Realizing the need for SOP to implement the NCrF a High-Level Committee (HLC) was constituted by the Ministry of Education with the help of three sub-committees to draft the SOPs for school education, higher education, and vocational education, training and skilling. These SOP will provide a clear guidelines to facilitate the assignment, accumulation, storage, transfer, and redemption of credits across school, higher, and vocational education and training. Equivalence and recognition of learning across different educational levels are essential for clear mobility. SOPs will address this more effectively with the help of the NHEQF, NSQF and NCF. This will create opportunities for learners for seamless lateral entry and credit transfer, promotion flexibility and optimizing learning pathways for students at all levels of education. This article introduces the learners and teachers at the higher at the higher educational level to know about the multiple entry and exit, recognition of prior learning, and work embedded programmes that offer opportunities for learners to develop essential skills. The SOPs at the higher educational level shall empower institutions to become hubs for skill development and offer diverse learning pathways for learners. All the higher educational institutions in the Country shall implement and practice these SOPs for implementation of NCrF in higher educational institutions to transform them into knowledge-driven, skill-centric, and future-ready educational centres.